PENGARUH KEADILAN DISTRIBUTIF DAN KEADILAN PROSEDURAL TERHADAP KINERJA KARYAWAN CV SINAR PUTRA MAHKOTA PONTIANAK - B31111021, Uswatun Hasanah (Jurnal Manajemen Update, 2017)
CV Sinar Putra Mahkota is a company engaged in the distributor, which has three divisions. This study aimed to analyze whether distributive justice and procedural fairness influence on employee performance CV Sinar Putra Mahkota Pontianak. The population in this study were employees of PT Sinar Putra Mahkota Pontianak is 62 and is taken as the respondent amounted to 54 people using the formula slovin. Data obtained through primary and secondary data. The data were analyzed using multiple linear regression analysis. Results from this study is that distributive justice and procedural fairness proven partially significant effect on employee performance CV Sinar Putra Mahkota Pontianak, thus it can be concluded that the employee's performance is influenced by two variables, namely distributive justice and procedural fairness. Keywords: Distributive Justice, Procedural Fairness, Employee Performance